Derivational affixes forming adjectives in class changing affixes found in nicola yoon’s novel entitled everything, everything - Satyartini, Ni Putu Diah; Putra, IGB Wahyu Nugraha; Sulatra, I Komang (Journal of Language and Applied Linguistics, 2022)
This study entitled “Derivational Affixes Forming Adjectives in Class Changing Affixes Found in Everything, Everything Novel. It is focused on derivational affixes in forming adjectives in class changing affixes. The aims of this study are to find out the types of derivational affixes forming adjectives and to analyze the kinds of class changing affixes forming adjectives found in Nicola Yoon’s Novel Entitled Everything, Everything. This study used theories from Katamba (1993) to classify the types of derivational affixes and McCarthy (2002) to analyze the kinds of class changing affixes forming adjectives. Descriptive and qualitative methods were used to analyze the data while observation methods were used to collect the data. The result found that there are 11 affixes attached with 143 words in forming adjectives with the occurrence as follows suffix –able (11 or 7,6%), -ing (1 or 0,6%), -ed (1 or 0,6%), -ful (45 or 31,6%),-ive (3 or 2,2%), -less (24 or 16,8%), -al (16 or 11,2%), -ic (6 or 4,2%), -ous (11 or 7,6%), -y (22 or 15,4%) and -ish (3 or 2,2%). Furthermore, there are 2 kinds of class changing affixes to form adjectives : adjectives derived from verbs with 19 frequency or 13,3% and adjectives derived from nouns with 124 frequency or 86,7%. Thus, the most frequently used affixes forming adjectives found in Everything, Everything Novel is suffix -ful with 45 or 31,6% and the mostly used class changing affixes to form adjectives is adjectives derived from nouns with 124 frequency or 86,7%.